Nitrogen Fixation - Nishibayashi, Yoshiaki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume presents a review of recent developments in nitrogen fixation using transition metal-dinitrogen complexes in the last decade. The authors are international experts in the corresponding field and each chapter discusses their latest achievements in the preparation of various transition metal-dinitrogen complexes and their reactivity. This volume will be helpful to researchers, teachers, and students who are interested in innovative and sustainable chemistry.
Determining and Understanding N-H Bond Strengths in Synthetic Nitrogen Fixation Cycles -- Dinitrogen Fixation by Transition Metal Hydride Complexes -- Reactivity of Group 5 Element Dinitrogen Complexes and N2-Derived Nitrides -- Functionalization of N2 by Mid to Late Transition Metals via N-N Bond Cleavage -- Synthetic Nitrogen Fixation with Mononuclear Molybdenum(0) Phosphine Complexes: Occupying the trans-Position of Coordinated N2 -- Catalytic Nitrogen Fixation Using Molybdenum-Dinitrogen Complexes as Catalysts -- Computational Approach to Nitrogen Fixation on Molybdenum-Dinitrogen Complexes -- Sulfur-Supported Iron Complexes for Understanding N2 Reduction -- Catalytic Transformations of Molecular Dinitrogen by Iron and Cobalt-Dinitrogen Complexes as Catalysts.
Keywords: Chemistry, Organic; Neurosciences; Organic Chemistry; Neuroscience